SOSIALISASI PERILAKU HIDUP BERSIH DAN SEHAT DI GAMPONG RABEU - Nanda Desreza; Rifka Annisa Mardhatillah; Indah Putri Rezeki; Riki Wan Redha; Dhea Natasha; Talitha Arista; Helmika Apri; Raja Aulia (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Health is a condition in which we are far from or free of diseases. Clean and Healthy Living Behavior (PHBS) is a lifestyle pattern that aligns with health guidelines to improve the quality of life. PHBS can be implemented in the community, households, and schools. PHBS encompasses various health behaviors performed consciously, allowing family members or individuals to take care of their own health and actively participate in community health initiatives. Socialization about Clean and Healthy Living Behavior (PHBS) has been carried out among the residents of Rabeu Village through methods such as lectures, discussions, and the use of poster media. The results indicate that, in general, the residents of Rabeu Village already understand the importance of maintaining environmental cleanliness and adopting clean and healthy living behaviors.